RELATIONSHIP BETWEEN PARAMETERS OF THE DENTAL APPARATUS AND RESPIRATORY ORGANS IN ORTHODONTIC TREATMENT - V.L. Bogdanov; T.A. Vyshemyrska; A.Ya. Grigorenko; N.N. Tormakhov; P.S. Flis (Український стоматологічний альманах)
The dental apparatus and the respiratory organs of the skull are closely related. Respiratory tract defects lead to mouth breathing and abnormalities in the development of the dental apparatus. Elimination of dental anomalies does not guarantee against recurrence of dental diseases and encourages the improvement of methods of comprehensive examination and diagnosis. There are many methods for determining the transverse parameters of the facial skull: by diagnostic models or by frontal teleradiography. These methods do not always reflect the true position of the facial skull. We have proposed a method of measuring the transverse dimensions of the upper jaw and upper respiratory tract using computed tomography, which through the use of appropriate mathematical modeling can improve the diagnosis of respiratory organs and dental apparatus during orthodontic treatment.